Photophysical and photochemical insights into the photodegradation of sulfapyridine in water: A joint experimental and theoretical study. (January 2018) - Zhang, Heming; Wei, Xiaoxuan; Song, Xuedan; Shah, Shaheen; Chen, Jingwen; Liu, Jianhui; Hao, Ce; Chen, Zhongfang
Abstract: For organic pollutants, photodegradation, as a major abiotic elimination process and of great importance to the environmental fate and risk, involves rather complicated physical and chemical processes of excited molecules. Herein, we systematically studied the photophysical and photochemical processes of a widely used antibiotic, namely sulfapyridine. By means of density functional theory (DFT) computations, we examined the rate constants and the competition of both photophysical and photochemical processes, elucidated the photochemical reaction mechanism, calculated reaction quantum yield ( Φ ) based on both photophysical and photochemical processes, and subsequently estimated the photodegradation rate constant. We further conducted photolysis experiments to measure the photodegradation rate constant of sulfapyridine. Our computations showed that sulfapyridine at the lowest excited singlet state (S1 ) mainly undergoes internal conversion to its ground state, and is difficult to transfer to the lowest excited triplet states (T1 ) via intersystem crossing (ISC) and emit fluorescence. In T1 state, compared with phosphorescence emission and ISC, chemical reaction is much easier to initiate. Encouragingly, the theoretically predicted photodegradation rate constant is close to the experimentally observed value, indicating that quantum chemistry computation is powerful enough to study photodegradation involving ultra-fast photophysical and photochemical processes. Graphical abstract: Image 1 Highlights: Systematically simulate both photophysical and photochemical processes of sulfapyridine. The rate constants for each photophysical process were calculated, the photoreaction mechanism was revealed. The theoretically predicted photodegradation rate constant agrees well with our experimental measurement. Theoretically predict the reaction quantum yield and the photodegradation rate constant under certain light irradiation.